ABR Obtained from Time-Efficient Train Stimuli for Cisplatin Ototoxicity Monitoring. - Dille, Marilyn F.; Ellingson, Roger M.; McMillan, Garnett P.; Konrad-Martin, Dawn (Journal of the American Academy of Audiology, 2013)
Background: Nonbehavioral methods for identifying cisplatin ototoxicity are important for testing patients with cancer who become too tired or sick to provide a reliable response. The auditory brainstem response (ABR) is a nonbehavioral test that is sensitive to ototoxicity but can be time consuming to implement over a range of frequencies and/or levels. To address this issue, trains of stimuli were developed that offer reliable ABR testing over a range of tone-burst frequencies and levels at a time savings of 77% relative to tone-burst stimuli presented individually. The clinical accuracy of this new method has yet to be determined on a clinical population. Purpose: This project was designed to determine the test performance of a time-effective ABR methodology aimed at identifying hearing shifts from cisplatin among veterans. A secondary goal was to determine whether improved test performance could be achieved by including our previously developed ototoxicity risk assessment model in the ABR prediction algorithm. Research Design: A set of discriminant functions were derived using logistic regression to model the risk for cisplatin-induced hearing change. Independent variables were one of several ABR metrics alone and combined with an ototoxicity risk assessment model that includes pre-exposure hearing and cisplatin dose. Receiver operating characteristic curve analysis was used to evaluate the test performance of these discriminant functions. Study Sample: Twenty-two male veterans treated with cisplatin for various cancers provided data from a total of 71 monitoring appointments. Data Collection and Analysis: Data were collected prospectively from one ear of each participant as designated below. Hearing shift was determined for frequencies within an octave of each patient's high-frequency hearing limit, tested in 1/6th-octave steps. ABRs were monitored using a set of two intensity trains from the highest two multiple frequency tone-burst center frequencies (up to 11.3 kHz) that yielded a robust response at baseline. Each intensity train was presented at 65--105 dB peSPL in 10 dB steps. Scorable ABRs were generally limited to the highest two intensities; therefore, analyses concern those levels. Results: The ABR measurement failure was high, up to 52% for some frequencies and levels. Furthermore, the ABR was not frequently obtained at levels below 85 dB peSPL, consistent with previous studies that suggest a stimulus level of greater than 80 dB peSPL is required to obtain a reliable response to trained stimuli. Using multivariate metrics that included the dose-ototoxicity model, the most accurate scoring function was change in amplitude at lowest half-octave frequency obtained at 105 dB (change in wave V amplitude at frequency 2/105). However, absence of wave V at a monitor patient visit of the ABR response at levels 105 or 95 dB peSPL was deemed the preferred scoring function, because it had lower measurement failure and was within one standard error of the most accurate function. Conclusions: Because of the large number of responses that could not be measured at baseline, this technique as implemented holds limited value as an ototoxicity-monitoring method.